Liver Function Test between Normotensive and Hypertensive Pregnant Women in those with Preeclampsia and Pregnancy-Induced Hypertension in Benin City, Nigeria - K. Atoe; E. O. Onovughakpo-Sakpa; E. S. Omozuwa; E. Ayinboumwan; O. O. Edenya; V. P. Orugbo; T. T. Selowo; O. Otokunefor (Journal of Applied Sciences and Environmental Management)
Hypertensive disorders of pregnancy, including preeclampsia and pregnancy-induced hypertension (PIH), are associated with liver dysfunction. Hence, the objective of this paper is to examine the differences in liver function test (LFT) parameters between normotensive and hypertensive pregnant women in those with preeclampsia and pregnancy-induced hypertension (PIH) in Benin City, Nigeria using appropriate standard methods by recruiting 190 participants: 124 with preeclampsia, 36 with PIH, and 30 normotensive controls. Liver function tests included serum alkaline phosphatase (ALP), aspartate aminotransferase (AST), alanine aminotransferase (ALT), bilirubin, and serum albumin. Results obtained showed significant differences were found in liver function test parameters among the three groups. Preeclampsia was associated with elevated AST (9.55 U/L), ALT (6.86 U/L), and ALP (46.51 IU/L) levels. PIH was characterized by elevated total bilirubin levels (2.34 mg/dL). Socio-demographic analysis revealed preeclampsia was more common among remarried individuals, while PIH was associated with lower secondary education levels. Obesity was linked to altered liver function in preeclamptic patients. This study highlights the importance of liver function tests in identifying pregnant women at risk of hypertensive disorders and related liver complications. The findings suggest that liver function test parameters can serve as useful biomarkers for early detection and management of hypertensive disorders of pregnancy.